Étude comparée des interrogateurs en lama et en français - Hanoukoume Cyril Kparou (European Scientific Journal, ESJ, 2018)
Interrogation is a Language Universal (LU), i.e., it exists in all natural languages. However, every language has undeniable particularities. Lama3 and French4, two languages from different language families, are a good illustration of these realities. A comparative study of interrogatives of both languages shows many similarities as well as dissimilarities. This article is aimed at presenting a comparative typology of interrogative markers and constructions in Lama and French. It consists of a morphosyntactic analysis of the interrogative markers and their different functions implied in the construction of interrogative sentences. French uses an interrogative copula est-ce que and the verbal inversion to form total interrogation, while Lama makes use of postpositional morphemes to formulate fundamental interrogation. Both languages form partial interrogation with adverbial and relative markers, but Lama goes further with the use of noun class interrogative markers. This study contributes to establish language universals and particularities in both languages at formal and functional levels.